Ratib al-Attas menurut perspektif al-Quran dan hadis - Mohsin, Mohd. Azman (Skudai Johor, 2016)
This article aims to evaluate the source of 17 dhikr in Ratib al-Άttas based on Quran, Hadith and scholar views on the meaning and purpose of dhikr. Applications Ratib al-Attas ceremony was conducted over 90 years ago in the state of Johor. In addition, the application Ratib al-Άttas assessment and justification is given from the perspective of Islamic practices. The method used is by clarifying the position of remembrance 17 Ratib al-Άttas more reliable by practitioners; avoid confusion and misunderstanding of the doctrine of Ratib al-Attas. The results showed that all 17 dhikr Ratib al-Άttas and the practice carried out are consistent with the arguments of al-Quran and Hadith. Based on this finding several suggestions is made to encourage the expend development of dhikr al-Άttas Ratib practice among the Muslim community in Malaysia.